2021
DOI: 10.1021/acs.langmuir.0c02416
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water Adsorption on the Frictional Properties of Hydrogenated Amorphous Carbon Films in Various Relative Humidities

Abstract: The tribological properties of hydrogenated amorphous carbon (a-C:H) films in ambient air were investigated from the microstructural point of view. a-C:H films with various microstructures (polymer-like, diamond-like, and graphite-like structures) were prepared, and the thickness of water adsorption layers on the films was measured. The adsorption behavior of water molecules on a-C:H films could be expressed with the Brunauer–Emmett–Teller (BET) isotherm, while the thicknesses of icelike and liquidlike water l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 61 publications
0
7
0
1
Order By: Relevance
“…Recently, friction and wear have become one of the major factors causing material and energy consumption. Lowering friction coefficient and wear rate are of great importance for improving the efficiency of metal-working processes [1] and prolonging the service life of mechanical equipment [2]. The adoption of appropriate lubricants is a powerful and convenient means to solve the issues.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, friction and wear have become one of the major factors causing material and energy consumption. Lowering friction coefficient and wear rate are of great importance for improving the efficiency of metal-working processes [1] and prolonging the service life of mechanical equipment [2]. The adoption of appropriate lubricants is a powerful and convenient means to solve the issues.…”
Section: Introductionmentioning
confidence: 99%
“…However, the a-C:F films showed a significant dependence on the RH, as shown in Figure e. Our previous study investigated the frictional characteristics of a-C:H films with a polymer-like structure (PLC films) and observed that the friction coefficient increased as the RH increased, although the measured O/C ratio was similar . The study revealed that the higher the RH, the thicker the adsorption water layer formed on the surface of the PLC films, which induced a high shear force between the water layers owing to the hydrogen bonds at the surface.…”
Section: Resultsmentioning
confidence: 91%
“…Our previous study investigated the frictional characteristics of a-C:H films with a polymer-like structure (PLC films) and observed that the friction coefficient increased as the RH increased, although the measured O/C ratio was similar. 29 The study revealed that the higher the RH, the thicker the adsorption water layer formed on the surface of the PLC films, which induced a high shear force between the water layers owing to the hydrogen bonds at the surface. Kim et al 37 conjectured that water layers possess large cohesive energy owing to greater dipole interactions, providing a stronger physical barrier, which is expected to result in a larger friction coefficient.…”
Section: ■ Results and Discussionmentioning
confidence: 96%
See 2 more Smart Citations